Clinical decision making in paediatric otitis media: A pilot quality improvement study. (January 2023) - Cleere, Eoin F.; Crotty, Thomas J.; Lang, John; Young, Orla; Keogh, Ivan J.
Abstract: Objectives: This study aimed to improve local management of paediatric otitis media using the 2022 American-Academy of Otolaryngology Head and Neck Surgery (AAO-HNS) Clinical Practice Guideline for Tympanostomy Tubes in Children. Methods: A SQUIRE 2.0 compliant quality improvement study was carried out within the outpatient department of our otolaryngology tertiary referral centre. Local outpatient management of paediatric otitis media was compared to the AAO-HNS guidelines, specifically focussing on the decision to offer tympanostomy tubes. Following initial audit of practice, an educational session was performed within the otolaryngology department and local practice was subsequently re-evaluated. Results: Overall, 88 children were included (46 pre-intervention and 42 post-intervention) with a mean age of 7.6 years (range 1–12 years). Sixty-four (72.7%) children presented with suspected otitis media with effusion. The remainder presented with recurrent or persistent acute otitis media (24/88, 27.3%). Twenty-six children were offered tympanostomy tubes (29.5%). Initial evaluation of practice identified that the decision to offer tympanostomy tubes was guideline appropriate in 76.1% of children (35/46). This significantly improved following an educational session (40/42, 95.2%, p = 0.02). The reasons for non-guideline compliance included: otitis media with effusion <3 months, no evidence of middle ear fluid and patients meeting criteria for tympanostomy tube insertion not being offered. Conclusions: A focussed educational intervention may improve local adherence to guidelines in the management of paediatric otitis media. Continued re-evaluation of local practice is essential in order to ensure children are managed in accordance with the guidelines.